Intercropping of upland cotton with cowpea cultivars - Beltrão, Napoleão E. de M.; Nóbrega, Laudemiro B. da; Azevêdo, Demóstenes M. P. de; Vieira, Dirceu J.; Crisóstomo, João R. (Pesquisa Agropecuaria Brasileira, 2014)
To study the behavior of annual cotton (Gossypium hirsutum L.r. latifolium Hutch.) CV. CNPA 2H in pure stand and intercropped with, four cowpea cultivars (Vigna unguiculata (L.)Walp. subsp. unguiculata), a field experiment was conducted during the rainy season of 1983, at Gurinhém, PB, Brazil. TV x 1836-013J was the less competitive cowpea cultivar tested, reducing cotton yield by only 13.8% and showed the lowest decrease of grain production (31.9%) when inter-cropped with cotton. Cotton + TV x 1836-013J resulted in a higher net income (33.41%) as compared to the only cotton system and had a LER of 1.56. The results showed, also, that Pitiúba was the most competitive cultivar reducing cotton yield by 33.1%. When cultivated in pure stand, CNC x 24-015E and CNC x 27-2E were the most productive cultivars with 1,210 and 1,127 kg/ha of grain, respectively.